2018
DOI: 10.1093/ehjqcco/qcy022
|View full text |Cite
|
Sign up to set email alerts
|

Time to hospital arrival among patients with acute myocardial infarction in China: a report from China PEACE prospective study

Abstract: https://clinicaltrials.gov/ct2/show/NCT01624909 ClinicalTrials.gov Identifier: NCT01624909.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
4
21
1
1
Order By: Relevance
“… 7 , 8 In other countries, the median pre-hospital delay time was 2 hours in Turkey, 23 2 to 5 hours in Sweden, 24 , 25 and 2.5 to 4 hours in China. 26 , 27 The mean age of the participants in this study was similar to that in a study in Malaysia. 28 Previous studies found that females were more likely to arrive late compared with males, but our findings failed to find statistically significant differences between males and females.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“… 7 , 8 In other countries, the median pre-hospital delay time was 2 hours in Turkey, 23 2 to 5 hours in Sweden, 24 , 25 and 2.5 to 4 hours in China. 26 , 27 The mean age of the participants in this study was similar to that in a study in Malaysia. 28 Previous studies found that females were more likely to arrive late compared with males, but our findings failed to find statistically significant differences between males and females.…”
Section: Discussionsupporting
confidence: 81%
“…28,33 Patients who perceived the symptoms as cardiac in origin were less likely to arrive late to a hospital. 27,34,35 A similar finding was reported in the current study.…”
supporting
confidence: 91%
“…Reperfusion injury is not a factor in the PL procedure, and thus the research focus is on the initial tissue injury response. However, although timely reperfusion is critical for human patients, studies have shown that a significant portion of patients receive therapy late, and 15-30% of patients are admitted to hospital too late after onset of the MI for reperfusion therapy to provide any benefit (Cohen et al, 2010;Gharacholou et al, 2010;Guan et al, 2018). Therefore, Gomez et al, 2008 C57/BL6 60 25% (n=9) 70% (n=15) Michael et al, 1995 FVB 30 60 13.7% (n=5) 20.5% n=762% (n=16) 66% (n=18) Michael et al, 1999 C57/BL6 120 30% (n=10) 60% (n=35) Yang et al, 2008 C57/BL6 45 25% n=8100% n=8a sizeable portion of the MI patient population experience a longterm ischaemic condition, for which modelling by the PL procedure could be more relevant.…”
Section: Clinical Relevancementioning
confidence: 99%
“…It has been reported that acute myocardial infarction contributes to high rates of morbidity and mortality in the past few decades in China [ 1 ]. In recent 20 years, the prompt myocardial revascularization can recover the myocardium blood flow and reduce ischemia-induced injury [ 2 ]. However, it may inevitably cause contractile dysfunction, severe arrhythmias, extremely to death, the complicated pathophysiological process of which was referred to as myocardial ischemia/reperfusion (I/R) injury [ 3 ].…”
Section: Introductionmentioning
confidence: 99%